Criteria for the Use of Adjustable Sutures in Surgical Treatment - Erkinovich, Kasimov Rayim (American Journal of Biomedicine and Pharmacy, 2025)
Adjustable suture techniques in ophthalmic surgery, particularly in strabismus correction, provide a refined method of achieving optimal ocular alignment and improved functional outcomes. The use of adjustable sutures enables postoperative adjustment of muscle position, reducing the rate of undercorrection and overcorrection. This article explores the criteria for selecting cases suitable for adjustable suture techniques, evaluates their clinical advantages, and identifies limitations. The analysis highlights the importance of patient age, cooperation, type of deviation, surgical indication, and postoperative adaptability. A comprehensive review of clinical experience and published data emphasizes that adjustable sutures represent a critical advancement in individualized surgical strategies for improving both functional and cosmetic outcomes in ophthalmology. Adjustable suture techniques in ophthalmic operations are considered a key advancement for achieving precise postoperative alignment, especially in patients with complex strabismus. This method enables surgeons to fine-tune muscle positioning after the procedure, thereby significantly lowering the rates of misalignment, undercorrection, and overcorrection that often follow conventional approaches. The adaptability of this method permits individualized treatment and better functional as well as cosmetic outcomes. The analysis underscores the criteria that make adjustable sutures suitable, including patient cooperation, type and severity of deviation, surgical indication, and overall adaptability to postoperative adjustment. Careful patient selection and surgeon expertise are essential in realizing the potential of this approach.